PENGARUH TATA KELOLA DAN KINERJA KEUANGAN TERHADAP FINANCIAL DISTRESS - Megita Dhisianti, Megita Dhisianti; Fujianti, Lailah; Munira, Mira (FEB-UP Press, 2024)
This study aims to analyze about the effect of profitability, leverage, firm size, institutional ownership, and the proportion of independent commissioners to financial distress conditions. This study took samples from manufacturing companies in the food and beverage industry subsector listed on the Indonesia Stock Exchange (BEI) for the period 2020-2022. The selection of samples in this study used purposive sampling. Based on determined criteria obtained a sample of 48 companies so that the observation data amounted to 144. The analysis method in this study used descriptive statistical analysis and logistic regression analysis. The tool for this study used SPSS 29 software. The results from this study show that profitability, leverage, and the proportion of independent commissioners have a significant effect on financial distress conditions, while firm size and institutional ownership do not have a significant effect on financial distress conditions. Keywords: Profitability, Leverage, Firm Size, Institutional Ownership, Proportion of Independent Commissioners, Financial Distress